Therapeutic potential of traditional Chinese medicine on heat stroke - Li, Lei; Wang, Man; Chen, Jikuai; Chen, Juelin; Wang, Yawei; Zhao, Minghao; Song, Qing; Xu, Shuogui (Frontiers in Pharmacology, 2023)
As global warming progresses, heat waves are becoming increasingly frequent and intense, meanwhile the incidence of heat stroke (HS) has increased sharply during the past decades. HS is typically associated with significant morbidity and mortality, and there is an urgent need for further research to solve this difficult issue. There currently exists difficulties regarding on-site emergency treatment methods and limited in-hospital treatment approaches, and better treatments are required as soon as possible. Theories and therapies from various traditional Chinese medicine (TCM) academic groups have been widely reported. Therefore, an exploration of prevention and protection methods should consider TCM experiences as an alternative. This article primarily reviews TCM herbal therapies and external therapies that have been described in various clinical reports and demonstrated in relevant studies. Herbal therapies, including herbal formulas, Chinese patent medicines (CPMs), single Chinese herbs, and associated extracts or monomers, are summarized based on the shared perspectives of the underlying mechanisms from TCM. In addition, external therapies including acupuncture, bloodletting, cupping, Gua sha and Tui na that have rarely been rarely mentioned and considered in most cases, are introduced and discussed to offer a unique perspective in the search for novel interventions for HS. In summary, TCM may provide abundant potential clinical benefits and research directions in the fight against HS.